Optimization of Electrocoagulation Conditions in the Degradation Process of Carbofuran Waste (Furadan 3GR) Using Al/Graphite Electrodes - Damar Nurwahyu Bima; Kumala Devi; Suhartana Suhartana; Sriyanti Sriyanti (ALCHEMY:Journal of Chemistry, 2023)
Electrocoagulation is one of the electrochemical methods for treating wastewater and separating pollutants. In this research, the electrocoagulation using Al/Graphite electrodes was applied to artistic wastewater containing carbofuran to see the reduction of its chemical oxygen demand(COD). The electrocoagulation process was chosen in this study based on several advantages, including easy to separate between impurities and the sample and a simple operating system. Several parameters such as electrolysis time, variations in electrolyte concentration, and the effect of pH have been investigated for their impact on the electrocoagulation process. The results showed that the proportion of the best reduction in chemical oxygen demand (COD) was 64.40%. The best conditions were an electrolysis time of 60 minutes, an electrolyte concentration of 0.15 M, and a pH of 10. The results also show that the decrease in chemical oxygen demand (COD) dependson those parameters. These results were investigated further by characterization using UV-Vis spectrophotometry and FTIR spectroscopy. The results of the UV-Vis spectrum showed a decrease in intensity at a wavelength of 275 nm. Analysis of the FTIR spectrum between the initial sample and the results of the electrocoagulation showed that there were similar absorption peaks but with much smaller intensity, indicating that the effluent's pollutants have been deposited.Keywords: Electrocoagulation, Carbofuran, Al/Graphite, COD